2008
DOI: 10.1007/s00540-008-0642-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of initial distribution volume of glucose to determine fluid volume loading in pulmonary thromboembolism and right ventricular myocardial infarction

Abstract: We report a case of acute right ventricular myocardial infarction (right AMI) following pulmonary thromboembolism (PTE). Following percutaneous coronary intervention, the patient was treated in our intensive care unit (ICU) with intraortic balloon pumping, anticoagulants, and plasma expansion. Fluid overload may cause a further leftward shift of the interventricular septum in patients with PTE, resulting in decreased cardiac output (CO). The initial distribution volume of glucose (IDVG) has been reported to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Data from the present study support these findings. When PPV over 11% is arbitrarily selected as the threshold of hypovolemia prediction based on literature reports [15,18], the optimal cutoff value of IDVG comparable to PPV in this study is 94.5 mL/kg, which is less than the lower limit of the normal IDVG range (110–130 mL/kg) [12,22]. Although PPV and SPV dynamic indices from respiratory variations strongly correlate with IDVG, the major limitations of routine clinical use of these indices are invasive arterial catheterization, expensive instruments, or specific software [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the present study support these findings. When PPV over 11% is arbitrarily selected as the threshold of hypovolemia prediction based on literature reports [15,18], the optimal cutoff value of IDVG comparable to PPV in this study is 94.5 mL/kg, which is less than the lower limit of the normal IDVG range (110–130 mL/kg) [12,22]. Although PPV and SPV dynamic indices from respiratory variations strongly correlate with IDVG, the major limitations of routine clinical use of these indices are invasive arterial catheterization, expensive instruments, or specific software [18].…”
Section: Discussionmentioning
confidence: 99%
“…More than 4000 IDVG determinations in an intensive care unit setting demonstrated that patients with an IDVG less than 100 mL/kg generally require fluid therapy [22]. Therefore, IDVG less than 100mL/kg was selected as the threshold for hypovolemia in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation